2021
DOI: 10.17079/jkgn.2021.23.3.249
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Tele-Consultation In Home-Visit Nursing Care Setting Under Korean Long-Term Care Insurance System

Abstract: Purpose: The National Health Insurance Service implemented a tele-consultation pilot project for in-home care using Information and Communication Technologies (ICTs). This study aims to investigate nurses’, doctors’, and families’ perceptions on the project.Methods: Using the pilot project database and perception survey data, this study provides a description of the satisfaction, re-participation motivation, and experiences of nurses, doctors, and families.Results: Tele-consultation for home-visit nursing was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…As of the end of December 2020, it was found that the relevant services had been provided to 169,391 out of the 1,591,827 health checkup result cases. [19][20][21][22][23] At the community level, regional health and medical institutions play an important role in reducing disease and enhancing health levels. Furthermore, the data linkage between each system can be effectively utilized because it has no data collection cost or responding burden.…”
Section: Introductionmentioning
confidence: 99%
“…As of the end of December 2020, it was found that the relevant services had been provided to 169,391 out of the 1,591,827 health checkup result cases. [19][20][21][22][23] At the community level, regional health and medical institutions play an important role in reducing disease and enhancing health levels. Furthermore, the data linkage between each system can be effectively utilized because it has no data collection cost or responding burden.…”
Section: Introductionmentioning
confidence: 99%